Pairing-up viologen cations and dications: a microscopic investigation of van der Waals interactions. Issue 44 (31st October 2018) - Gourlaouen, Christophe; Vela, Sergi; Choua, Sylvie; Berville, Mathilde; Wytko, Jennifer A.; Weiss, Jean; Robert, Vincent
Abstract : Polarizability and simultaneous environment effects overcome Coulomb repulsions. Abstract : The microscopic origin of van der Waals- and magnetic-interactions in 4, 4′ methyl viologen cation-based units (MV + ˙ and MV 2+ ) was inspected using wave function (variational DDCI and perturbative MP2, CASPT2) and density functional theory (DFT) calculations. The analysis deepens the comprehension of the magnetic behavior of experimental bis-viologen cyclophanes ([CYC] 2(+ ˙ ) ), in which the MV + ˙ units are connected through alkyl linkers of different lengths. The formation of the so-called long-multicenter bonds in such radical dimers, responsible for the quenching of the magnetic response, was analyzed in [MV2 ] 2(+ ˙ ) . Dynamical correlation effects, accessible from second-order perturbation corrections, were decisive in observing a bonding regime characterized by an equilibrium distance of 3.3 Å and a 45 kJ mol −1 dissociation energy. At larger intermolecular distances, our calculations on [MV2 ] 2(+ ˙ ) indicate that the singlet and triplet states are energetically competing ( i.e. weak exchange interactions, J AB ). Despite the absence of any clear bonding regime at the MP2 level, the puzzling association of two di-cations into [MV2 ] 4+ is anticipated at 3.3 Å using weakly screened point charges ( ε = 1.5) to account for the Coulomb interactions between the solvated subunits. The main conclusion is that both dispersion interactions and environment effects are required to overcome the Coulomb repulsion associated with doubly-charged species. All these data provide some complementary insights into the nature and amplitude of interactions between cation and dication units, and their relevance in various experimental manifestations.